Clinical Course of Interstitial Lung Disease in Patients With Rheumatoid Arthritis - Eric L. Matteson; Elisabeth Bendstrup; Mary E. Strek; Philippe Dieudé (ACR Open Rheumatology)
Interstitial lung disease (ILD) is a frequent manifestation of rheumatoid arthritis (RA) that is associated with high mortality. RA‐ILD may initially be asymptomatic, and lung function may be markedly impaired by the time it is diagnosed. The course of RA‐ILD is highly variable, with some patients experiencing no discernable progression or a slow decline, whereas others experience more rapid deterioration. Some patients develop progressive pulmonary fibrosis, which is associated with high mortality. Although risk factors for the progression of RA‐ILD have been identified, including older age, worse lung function, and a usual interstitial pneumonia pattern on high‐resolution computed tomography, it is not possible to predict the course of RA‐ILD in an individual patient. The association between RA disease activity and progression of RA‐ILD remains unclear. Regular monitoring is important to enable the prompt identification of progression and early intervention to preserve lung function. The management of RA‐ILD requires a multidisciplinary and individualized approach, taking account of the severity and progression of articular and lung disease, risk factors for the progression of RA‐ILD, and the patient's preferences, and may include immunosuppression, antifibrotic therapy, and supportive care.